Genome sequence data reveal at least two distinct incursions of the tropical race 4 (TR4) variant of Fusarium wilt into South America - Reyes Herrera, Paula H.; Torres Bedoya, Eliana; Lopez Alvarez, Diana; Burbano David, Diana; Carmona, Sandra L.; Bebber, Daniel P.; Studholme, David J.; Betancourt, Monica; Soto Suarez, Mauricio (Cold Sprimg Harbor Laboratory - CSH, 2025)
The global banana industry is threatened by one of the most devastating diseases: Fusarium wilt (FWB). FWB is caused by the soil-borne fungus Fusarium oxysporum f. sp. cubense (Foc), which almost annihilated the banana production in the late 1950s. A new strain of Foc, known as tropical race 4 (TR4), attacks a wide range of banana varieties including Cavendish clones which are the source of 99% of banana exports. In 2019, Foc TR4 was reported in Colombia, and more recently (2021) in Peru. In this study, we sequenced three fungal isolates identified as Foc TR4 from La Guajira (Colombia) and compared them against 19 whole-genome sequences of Foc TR4 publicly available, including four genome sequences recently released from Peru. To understand the genetic relatedness of the Colombian Foc TR4 isolates and those from Peru, we conducted a phylogenetic analysis based on a genome-wide set of single nucleotide polymorphisms (SNPs). Additionally, we compared the genomes of the 22 available Foc TR4 isolates looking for the presence-absence of gene polymorphisms and genomic regions. Our results reveal that (i) the Colombian and Peruvian isolates are genetically distant, which could be better explained by independent incursions of the pathogen to the continent, and (ii) there is a high correspondence between the genetic relatedness and geographic origin of Foc TR4. The profile of present/absent genes and the distribution of missing genomic regions showed a high correspondence to the clades recovered in the phylogenetic analysis, supporting the results obtained by SNP-based phylogeny.